Preventive Effect of an Intervention Program with Increased Physical Activity on the Development of Musculoskeletal Pain in Community-Dwelling Older Adults: A Randomized Controlled Trial. Issue 5 (2nd November 2022) - Hirase, Tatsuya; Inokuchi, Shigeru; Koshikawa, Shota; Shimada, Hinata; Okita, Minoru
Abstract: Objective: To examine whether compared with a program without increased physical activity, an intervention program with increased physical activity can prevent the development of musculoskeletal pain in community-dwelling older adults. Design: Randomized controlled trial. Setting: Japanese community. Subjects: Seventy-nine older adults without musculoskeletal pain were randomized into two groups: an intervention group (n = 40) that engaged in increased physical activity and an exercise class and a control group (n = 39) that participated only in the exercise class. Methods: The exercise class consisted of weekly 60-min sessions over 24 weeks. The program to increase physical activity required the participants to record their daily step counts using pedometers. The primary outcome was the development of musculoskeletal pain, and secondary outcomes were physical function, psychological status, cognitive function, and physical activity levels. Results: Twenty-four weeks after the intervention, the intervention group had a significantly lower prevalence of musculoskeletal pain (12.8%) than the control group (32.4%; P  =   .040). A time-by-group interaction emerged for cognitive function ( P  =   .01) and physical activity levels ( P  <   .001), both of which favored the intervention group. The intervention group also showed greater improvement in psychological status 24 weeks after the intervention than the control group ( P  =   .018). Conclusions: The intervention program with increased physical activity prevented the development of musculoskeletal pain and improved cognitive function, physical activity levels, and psychological status more effectively than the program without increased physical activity. Our intervention program may be an effective pain prevention approach for older adults. Trial registration: UMIN000032768; registered on June 1, 2018.